THE ROLE OF THE MEDIA IN ENCOURAGING AND STRENGTHENING HUMAN RIGHTS ENFORCEMENT IN THE DIGITAL POLITICAL ERA - Yose Indra pratama; Admiral Qurrotul Annisa (JURNAL SETIA PANCASILA, 2024)
This article aims to provide a deeper understanding of how the challenges of the digital era can impact human rights and how the law can be used as a tool to protect these rights. Additioly the article also calls for legal solutions that help maintain a balance between technological innovation and the protection of human rights. The main part of this article was prepared using a reading/writing approach or literature review using various secondary library sources to answer all the research questions conducted. The results of a study of the challenges and legal solutions for protecting human rights in the digital era show that although the challenges of protecting human rights in the digital era are very complex, there are intelligent and effective legal solutions that can overcome these challenges, showing that this can contribute to the protection of human rights. balance between technology and technology. Innovation and individual rights.